Metaphor in the Novel Lelaki Harimau by Eka Kurniawan: A Semantic Study - Belwawin, Levina Novita; Somelok, Grace; Rutumalessy, Merlyn (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this study is to describe the metaphor in the novel Lelaki Harimau by Eka Kurniawan, First Edition August 2014. Publisher of PT Gramedia Pustaka Utama. This type of research is qualitative with descriptive methods. Qualitative research is research that intends to understand the phenomena about what is experienced by research subjects, such as actors, perceptions, motivations, and actions, in an olistic manner and by means of descriptions in the form of words and languages in a special natural context by utilising various natural methods. The results of this study will present some data obtained as research evidence, namely, the types of metaphors contained in the novel, which consist of orientational metaphors and ontological metaphors.